Características del proceso enseñanza-aprendizaje de la asignatura de informática en el segundo año de bachillerato del Colegio Nacional Mixto Nocturno Kleber Franco Cruz, del cantón Machala, provincia de El Oro, periodo lectivo 2009-2010. - Ramírez Aguilar, Ana Paola (2011)
The present research work whose theme is: "CHARACTERISTICS OF THE TEACHING-LEARNING PROCESS OF THE COMPUTER COURSE IN THE SECOND YEAR OF BACHELOR OF THE NATIONAL MIXED NATIONAL SCHOOL KLEBER FRANCO CRUZ, DEL CANTÓN MACHALA, PROVINCE OF EL ORO, LECTURE PERIOD 2009-2010 "Is aimed at making teachers aware of the task that is being undertaken each day towards the attainment of the objectives of education, valuing the educational activity to carry out an effective exercise of the teaching-learning process.